DNATRANSFECTION OF ANIMAL CELLS AS ATOOL USED IN ANIMAL BIOTECHNOLOGY - Iglesias Artola, Juan M. (2015)
Transfection is a process that involves inserting nucleotides into a cell, with the final product being transgenesis. In recent decades different methods have been developed such as biological, physical and chemical processes that have allowed the introduction of nucleotides into cells. In this review, some important aspects of the most used transfection methods in recent years, and their efficiency in the development of the industry, will be addressed. It concludes with an analysis of the ethical debates that have been generated within the field of animal biotechnology.